Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2000)
Table of Content Brasilian Concrete Poetry by Vincent Katz Body Malaise – Annette Messager’s Anatomical Theater by Elisabeth Bronfen Maurizio Cattelan A Grammar of Visual Delinquency by Nicolas Bourriaud A Sociology Without Truth by Alison Gingeras Every Artist Can Be a Man by Francesco Bonami Yayoi Kusama Between Heaven and Earth: This Languid Weight of Life by Usula Panhand-Bühler Beyond Oedipus: Desiring Production of Yayoi Kusama by Midori Matsui Three Thoughts on Femininity, Creativity and Elapsed Time by Grisela Pollock Kara Walker Final Cut by Gwendolyn Dubois Shaw As American as Apple Pie by Elizabeth Janus Nigger Lover or Will There Be Any Black People in Utopia? by Hamza Walker Andreas Züst, Insert Anna Gaskell’s Girl Art by Jan Avgikos Back to the Future, Les Infos du Paradis by Ali Subotnick Cumulus from America by Margit Rowell The Difficulty of Dialogue, Cumulus from Europe by László F. Földényi The Now Idea: Embroidery by Michelle Nicol
As early as the sixties, Japanese artist Yayoi Kusama’s elaborate masquerades already caused a stir when discovered by the New York art world. The recent revival of interest in this artist, as evidenced by a number of important exhibitions and publications, is but appropriate to an intricate oeuvre, energized by unsuspected, wild and beautiful currents. At the same time, her works raise questions aimed at basic social issues and conventions which also govern art. In this edition of Parkett, much is said about anguish—but not about that of expressionist art. In her essay on Kara Walker, Gwendolyn Dubois Shaw discusses the anguish of having to establish identity as an Afro-American woman and artist, and places this quest within the broader context of “the pain of self-performance and of artistic commodification.” Griselda Pollock also speaks of the “titanic struggle with pressures” that assail Yayoi Kusama both from within and without. By comparison Maurizio Cattelan would appear to be a buoyant player, were it not for the burden of impossibility that lurks behind his skepticism. As Alison Gingeras writes, he “disavows the role of the artist as guardian of the Enlightenment ideals of moral rationality, historical consciousness, and truth. Instead his sociology-sans-truth sets into motion a much more disruptive scenario.” (editorial by publisher)
boek
Keywords: Cattelan, Maurizio; Walker, Kara; Kusama, Yayoi